CO oxidation activity of thermally stable Fe–Cu/CeO2 catalysts prepared by dual-mode arc-plasma process1. Issue 8 (21st August 2015) - Hinokuma, Satoshi; Yamashita, Noriko; Katsuhara, Yasuo; Kogami, Hayato; Machida, Masato
<x xml:space="preserve">Abstract</x> Fe–Cu bimetal nanoparticles were prepared by the dual-mode arc-plasma process. The CO oxidation activity of Fe–Cu/CeO2 was enhanced by thermal aging at 900 °C. CO oxidation over aged Fe–Cu/CeO2 proceeded via the Mars–van Krevelen mechanism.